Fast photothermal spatial light modulation for quantitative phase imaging at the nanoscale - Robert, Hadrien M L; Holanová, Kristýna; Bujak, Łukasz; Vala, Milan; Henrichs, Verena; Lánský, Zdeněk; Piliarik, Marek (Nature communications, 2021)
Spatial light modulators have become an essential tool for advanced microscopy, enabling breakthroughs in 3D, phase, and super-resolution imaging. However, continuous spatial-light modulation that is capable of capturing sub-millisecond microscopic motion without diffraction artifacts and polarization dependence is challenging. Here we present a photothermal spatial light modulator (PT-SLM) enabling fast phase imaging for nanoscopic 3D reconstruction. The PT-SLM can generate a step-like wavefront change, free of diffraction artifacts, with a high transmittance and a modulation efficiency independent of light polarization. We achieve a phase-shift > π and a response time as short as 70 µs with a theoretical limit in the sub microsecond range. We used the PT-SLM to perform quantitative phase imaging of sub-diffractional species to decipher the 3D nanoscopic displacement of microtubules and study the trajectory of a diffusive microtubule-associated protein, providing insights into the mechanism of protein navigation through a complex microtubule network.
Keywords: Microtubule-Associated Proteins; proteiny buněčného cyklu; Light; Nanotechnology; zlato; nanotrubičky; Tubulin; Cell Cycle Proteins; mikrotubuly; Microtubules; Imaging, Three-Dimensional; kovové nanočástice; Humans; Computer Simulation; časové faktory; Schizosaccharomyces pombe Proteins; světlo; Microscopy, Phase-Contrast; Microscopy, Interference; mikroskopie atomárních sil; tubulin; lidé; mikroskopie fázově kontrastní; interferenční mikroskopie; optické jevy; Optical Phenomena; Time Factors; zobrazování trojrozměrné; Nanotubes; počítačová simulace; proteiny asociované s mikrotubuly; Schizosaccharomyces pombe - proteiny; Microscopy, Atomic Force; Metal Nanoparticles; nanotechnologie; Gold